INTERNATIONAL COMPARATIVE ANALYSIS OF NATIONAL STATE ELECTRONIC EDUCATIONAL PLATFORMS FOR SCHOOLCHILDREN - Fiofanova; Bokova; Morozova (Revista Inclusiones, 2020)
Developing electronic educational platforms for organizing the education of schoolchildren in different countries are considered. The purpose of the study was to conduct a comparative analysis of national electronic educational platforms by parameters: the organizational structure of electronic educational platforms, the functionality of user interfaces, educational data analytics programs, the possibilities and directions of using the results of educational data analysis. The paper actualizes the issues of the need to develop a new field of pedagogical knowledge – “Pedagogy based on data”. The new field of knowledge is aimed at the development of methodology and technologies for the analysis of educational data, which is accumulated in the form of students’ “digital traces” on electronic educational platforms.